Ergonomic Exercises to Lower Uric Acid Levels in the Elderly with Gout - Muji Hartinah; Suharti Suharti; Elsa Gusrianti; Santa Novita Yosephin Silalahi (Aloha International Journal of Health Advancement (AIJHA), 2024)
Ergonomic gymnastics is a practical and effective method to maintain a healthy body. The movements contained in ergonomic gymnastics are movements that are very effective, efficient, and logical because they use a series of movements that have been carried out by humans from the past until now. Ergonomic gymnastic movements are in accordance with the rules of body creation, and are inspired by the "prayer" movement in Islam. This study aims to determine the effect of ergonomic exercise on uric acid levels in the elderly with gout at "Rumah Bahagia Bintan", Indonesia. The design of this research was one group pretest-posttest. Research respondents were 16 elderly who were selected by total population sampling technique. In the phase before and after the intervention, blood uric acid levels were measured. Furthermore, the data were analyzed by paired sample t-test. The results of the analysis showed that the p value = 0.003, so it was interpreted that there was a difference in uric acid levels between before and after ergonomic exercise. Furthermore, it was concluded that ergonomic exercise was effective in reducing blood uric acid levels in the elderly with gout. Keywords: elderly; gout; blood uric acid; ergonomic exercise